Litciae Flour / Nurul Izzati Medihi - Medihi, Nurul Izzati; Rasli, Nurul Husna Rashiqah; Mohammad Nadzree, Nurul Afiqah; Harun, Nur Nael ‘Awateef; Mohamad Dashuki, Siti Nur Aisyah (2021)
Flour is a key ingredient in many foods including breads, desserts and noodles. It is often used as a thickener in sauces and soups as well. Typically, flour is made from wheat which possesses a good amount of gluten to give texture and elasticity to the foods. Although it is unproblematic for many, people with celiac disease, non-celiac gluten sensitivity or those avoiding gluten for other reasons should not consume the wheat flour. Hence, a variety of gluten-free alternatives to regular wheat flour have been produced. However, the common problems of currently available gluten-free flours are they are expensive and have texture issues such as reduced elasticity and increased cooking losses in pasta. Therefore in order to tackle these issues, we introduced LitCiae flour. LitCiae flour is technically produced by grinding raw seeds of engkala fruit (Litsea garciae). Engkala fruit is a well known native fruit in West Malaysia, Sarawak and Sabah. The fruit is round, pink and has white flesh with creamy texture and flavour that resembles avocado. Like the avocado, the engkala fruit is very nutritious containing high natural antioxidants, protein, vitamins and minerals. Additionally, its raw seed also possesses a good amount of antioxidant and minerals as well as higher protein and fibre content (Hussen, 2015). However, the seeds are usually thrown away as they are inedible. Thus, to make it suitable for consumption, the seeds need to be processed first. In fact, the existence of the LitCiae flour can maximize the utilisation of the fruit and be a solution to food waste especially during in season. Therefore, the process of making LitCiae flour involves cleaning, washing, cutting, crushing, dewatering, drying and sieving the seeds to produce a fine LitCiae flour. LitCiae flour is a gluten-free flour. Thus, it can be consumed by people with celiac disease, non-celiac gluten sensitivity or those avoiding gluten for other reasons. This flour also can be used to produce pasta with an excellent quality and taste as good as pasta made from semolina flour. We developed an anti-clump technology (GelaTech) where the LitCiae flour will undergo the gelatinization process to avoid clumpiness. The cooking of pre-gelatinized flour will produce a dough with even heat and moisture distribution and clump-free pasta.